Дослідження тривалості технологічної перерви між нанесенням шарів реставраційної штукатурки - Уманець, І. М. (Ways to Improve Construction Efficiency, 2014)
Investigations of the research of a technological break between coats of plaster restoration to adopt technological solutions with its devices.